2017
DOI: 10.1016/j.bbmt.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical Bone Marrow Transplantation with Post-Transplant Cyclophosphamide for Children and Adolescents with Fanconi Anemia

Abstract: We describe haploidentical bone marrow transplantation with post-transplant cyclophosphamide (PT-CY) for 30 patients with Fanconi anemia (FA). Twenty-six patients were transplanted upfront, and the preparatory regimens included fludarabine 150 mg/m + total body irradiation 200 to 300 cGy ± CY 10 mg/kg without (n = 12) or with rabbit antithymocyte globulin (r-ATG) 4 to 5 mg/kg (n = 14). Four patients were rescued after primary or secondary graft failure after related or unrelated donor transplantation with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
45
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 36 publications
3
45
3
5
Order By: Relevance
“…The additional effect of ATG in a Post‐Cy‐based regimen era is controversial. Bonfim et al reported lower GVHD rates and higher survival in Fanconi anemia patients receiving ATG treatment with Post‐Cy. However, we have not found such an effect in our study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The additional effect of ATG in a Post‐Cy‐based regimen era is controversial. Bonfim et al reported lower GVHD rates and higher survival in Fanconi anemia patients receiving ATG treatment with Post‐Cy. However, we have not found such an effect in our study.…”
Section: Discussionsupporting
confidence: 82%
“…The usual recommendation for GVHD prophylaxis in Post‐Cy practice is to administer cyclophosphamide on day 3 with or without day 4 and to start a calcineurin inhibitor the day after the last dose of cyclophosphamide, with or without mycophenolate . Our approach differs from these literature standards in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, for many years, UCB was easier and faster, and therefore used in almost 40% of our patients. More recently, haploidentical transplants with in vivo T cell depletion with post-transplant cyclophosphamide (PTCy) have been described in children and adults with hematological malignancies and non-malignant diseases [38][39][40][41][42][43]. This strategy is cheap and immediately available, and its applicability to treat PIDs has been reported in a small number of patients, but results are promising [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…12 Similarly, Shima reported the combination of TBI with melphalan. 13 The usage of TBI as a part of haploSCT with a PTCY regimen is continued even in patients with Fanconi anemia 14,15 or in combination with busulfan. 16 Some reports in adults have investigated the possibility of a TBI-free conditioning regimen by replacing it with thiotepa and melphalan, but the trial was complicated by limited access to thiotepa and the group reversed to TBI.…”
Section: Discussionmentioning
confidence: 99%